Reduced Sleep Duration and Sleep Efficiency Were Independently Associated With Frequent Nightmares in Chinese Frontline Medical Workers During the Coronavirus Disease 2019 Outbreak - Lin, Yi-Qi; Lin, Ze-Xin; Wu, Yong-Xi; Wang, Lin; Zeng, Zhao-Nan; Chen, Qiu-Yang; Wang, Ling; Xie, Xiao-Liang; Wei, Shi-Chao (Frontiers in Neuroscience, 2021)
Objectives: Nightmares were related to emotion and behavior problems and also emerged as one of core features of post‐traumatic stress disorder (PTSD). Our study aimed to investigate the associations of frequent nightmares with sleep duration and sleep efficiency among frontline medical workers in Wuhan during Coronavirus Disease 2019 (COVID-19) outbreak. Methods: A total of 528 healthcare workers from the province of Fujian providing medical aid in Wuhan completed the online questionnaires. There were 114 doctors and 414 nurses. The age, sex, marriage status and working situation were recorded. A battery of scales including Pittsburgh Sleep Quality Index (PSQI) and 12-item General Health Questionnaire (GHQ-12) was used to evaluate subjects’ sleep and general mental health. Frequent nightmares were defined as the response of at least once a week in the item of “nightmare” of PSQI. Results: Frequent nightmares were found in 27.3% of subjects. Frequent nightmares group had higher score of PSQI-sleep duration and PSQI-habitual sleep efficiency (frequent nightmares vs non-frequent nightmares: PSQI-sleep duration: 1.08±0.97 vs 0.74±0.85, P<0.001; PSQI-habitual sleep efficiency: 1.08±1.10 vs 0.62±0.88, P<0.001). Reduced sleep duration and reduced sleep efficiency were independently associated with frequent nightmares after adjustment for age, sex, poor mental health and regular sleeping medication uses (reduced sleep duration: OR: 1.96, 95% CI:1.07-3.58, P=0.029; reduced sleep efficiency: OR: 2.17, 95% CI:1.09-4.32, P=0.027). Subjects with both reduced sleep duration and sleep efficiency were also associated with frequent nightmares (OR: 2.70, 95% CI:1.57-4.65, P<0.001). Conclusions: The present study found that sleep duration and sleep efficiency were both independently associated with frequent nightmares among frontline medical workers in Wuhan during COVID-19 pandemic. Nightmares and even following PTSD symptoms need to be paid attention to among subjects with reduced sleep duration or sleep efficiency facing potential traumatic exposure.